PERSEPSI & EKSPEKTASI WISATAWAN TERHADAP PELAYANAN HOTEL MELATI DI KAWASAN UBUD KABUPATEN GIANYAR - Dewa Gede Putra; I Wayan Pantiyasa (Jurnal Ilmiah Hospitality Management, 2014)
In general this research aims at knowing tourist perception toward the service provided by the small (melati) hotels around Ubud area;Â  knowing the most influential indicators toward the service of small (melati) hotels in Ubud area. Total samples of the research area 38 melati hotels, while total of respondents are 399 tourists. Researched variables/indicators are 21 indicators wich are related to service dimensions (servqual), namely direct form/proof dimensions tangible, reliability, responsivenees, assurance, and empathy. Analysis applied for this research is the frequency distribution to know how important or how good the service is offered, and performance-importance analysis to rank all the quality determining variables and to indentify actions.The result of servqual analysis shows that all variables/indicators indicate satisfying performances, in which average scores of perception (performance) are bigger than average scores of expectation (necessity) which means satisfied. Therefore, it can be said that guests staying at melati hotels in Ubud area state that the hotel services are satisfying. The result of the importance-performance analysis shows that from 21 variables/indicators evaluated, none of the service indicator exists on quadrant 1 (main priority), 10 service indicators exist on quadrant 2 (maintain achievement), 8 indicators exist on quadrant 3 (low priority), and 3 indicators exist on quadrant 4 (excessive). Whereas, the service indicators of melati hotels which are most influential according to guest evaluation, are such those shown in quadrant 2, namely: commitment realization, sympathetic attitude towards guests, service offered rightly, service offered at the time agreed, accurate noting system, staff willing to assist guests, reliable staff, comfortable feeling on transaction, friendly attitude of staff, and well-knowledgeable staff.